نماذج من الأساليب النبوية وعلاقتها بالأساليب التدريسية المعاصرة - Ibtissem Ghanem (UIN Fatmawati Sukarno Bengkulu, 2019)
The current research paper aims to identify the Prophet’s Mouhamed (PBHU) characteristics and styles and its relation into contemporary teaching methods by mentioning examples from his Prophetic Tradition (Sunnah) .The study was limited to the Prophet's Mouhamed methods in the field of education as: problem solving, conceptual maps and brainstorming. One of the findings said that the Prophet Mouhamed (PBUH) drew the basic principles of contemporary teaching methods, and his Prophetic Tradition is rich with different teaching methods which consequently should be used for identifying and applying other methods in the field of education.